From Training and Motivation to Entrepreneurial Intention: Unpacking the Role of Educational Mediation in University Entrepreneurship - Putrianti, Flora Grace; Nurdiansyah, Yanuar; Wisnu Ardhi, Ovide Decroly (Indonesian Journal of Business and Entrepreneurship Research, 2025)
Unemployment remains a major challenge in Indonesia, primarily due to the country’s high population growth rate, which intensifies competition in the job market. One effective strategy to address this issue is by increasing the number of entrepreneurs. This study aims to examine the direct and indirect effects of entrepreneurship training, motivation, and entrepreneurial environment on students’ entrepreneurial intention, with entrepreneurship education serving as a mediating variable. A quantitative approach with a descriptive explanatory design was employed, involving a population of 492 students. A sample of 103 students from the Faculty of Economics and Business, Universitas Negeri Makassar, was selected using proportional random sampling. Data analysis reveals that entrepreneurship training, motivation, and the entrepreneurial environment significantly influence entrepreneurial intention both directly and indirectly through entrepreneurship education. The findings highlight the importance of structured entrepreneurial education as a pathway to strengthen students' business skills and intentions. These insights can serve as valuable input for educators in guiding students not only in product development but also in marketing, business evaluation, and strategic growth. Future research is encouraged to expand the scope by incorporating additional variables and diverse methodological approaches.